"Scholarly Caution": Challenges and Traps in New Cultural History Studies - Zhang, Xuejian (Journal of Theory and Practice of Social Science, 2023)
In new cultural history studies, the materials, methods and approaches are all different from conventional ones, which asks scholars to be more cautious when conducting their researches. By analyzing various cases, this paper gives an explanation of what "scholarly caution" is and what scholars should do to avoid potential mistakes.